Pandemic origins and a One Health approach to preparedness and prevention: Solutions based on SARS-CoV-2 and other RNA viruses - Keusch, Gerald T; Amuasi, John H; Anderson, Danielle E; Daszak, Peter; Eckerle, Isabella; Field, Hume; Koopmans, Marion; Lam, Sai Kit; Das Neves, Carlos G; Peiris, Malik; Perlman, Stanley; Wacharapluesadee, Supaporn; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
COVID-19 is the latest zoonotic RNA virus epidemic of concern. Learning how it began and spread will help to determine how to reduce the risk of future events. We review major RNA virus outbreaks since 1967 to identify common features and opportunities to prevent emergence, including ancestral viral origins in birds, bats, and other mammals; animal reservoirs and intermediate hosts; and pathways for zoonotic spillover and community spread, leading to local, regional, or international outbreaks. The increasing scientific evidence concerning the origins of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is most consistent with a zoonotic origin and a spillover pathway from wildlife to people via wildlife farming and the wildlife trade. We apply what we know about these outbreaks to identify relevant, feasible, and implementable interventions. We identify three primary targets for pandemic prevention and preparedness: first, smart surveillance coupled with epidemiological risk assessment across wildlife-livestock-human (One Health) spillover interfaces; second, research to enhance pandemic preparedness and expedite development of vaccines and therapeutics; and third, strategies to reduce underlying drivers of spillover risk and spread and reduce the influence of misinformation. For all three, continued efforts to improve and integrate biosafety and biosecurity with the implementation of a One Health approach are essential. We discuss new models to address the challenges of creating an inclusive and effective governance structure, with the necessary stable funding for cross-disciplinary collaborative research. Finally, we offer recommendations for feasible actions to close the knowledge gaps across the One Health continuum and improve preparedness and response in the future.